2018
DOI: 10.1002/jia2.25065
|View full text |Cite
|
Sign up to set email alerts
|

Completion of the tuberculosis care cascade in a community‐based HIV linkage‐to‐care study in South Africa and Uganda

Abstract: IntroductionTuberculosis (TB) is the leading cause of HIV‐associated mortality in Africa. As HIV testing, linkage to care and antiretroviral treatment initiation intensify to meet UNAIDS targets, it is not known what effect these efforts will have on TB detection and prevention. We aimed to characterize the TB care cascade of screening, diagnostic testing, treatment and provision of isoniazid preventive therapy (IPT) in a study of community‐based HIV screening and linkage to care and determine whether symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
1
16
1
Order By: Relevance
“…Finally, because intervention households were distributed among 17 CHWs, some CHWs only rarely collected sputum, limiting the opportunities to gain proficiency. Low success rates of sputum collection have been observed in other similar settings [9], including among PLWHs [24]. Future studies should evaluate strategies to promote health worker confidence and competence in sputum collection, including delivery of instructional videos via phones or tablet computers [25].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, because intervention households were distributed among 17 CHWs, some CHWs only rarely collected sputum, limiting the opportunities to gain proficiency. Low success rates of sputum collection have been observed in other similar settings [9], including among PLWHs [24]. Future studies should evaluate strategies to promote health worker confidence and competence in sputum collection, including delivery of instructional videos via phones or tablet computers [25].…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines suggest clinicians should follow a series of steps spanning assessment, diagnosis and treatment, which can be represented in a care cascade. Cascades have been extensively used in HIV studies to describe quality of care [1721], and are now increasingly used in TB care [2225]. We identified one study using the cascade concept in paediatric TB [26] and another in adolescent TB [27] but none specifically looking at paediatric in-patient care.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a lot more PLHIVs (210%) were sent to the TB diagnostic unit for definitive TB diagnosis than the number that received clinical screening. This is contrary to documentations in pilot programs in Sub-Saharan Africa where the true cascade is followed through, many of them showing far less presumptive TB patients reaching the diagnostic point than the number originally screened positive for TB [10]. Der et al (2020) showed in a similar cascade analysis in rural and urban Ghana that most of the losses are due to the long travel distance between the service delivery points [11].…”
Section: Fig 3 Intensified Case Finding Of Tb Among Plhivs By Art Smentioning
confidence: 86%